PERFORMANCE EVALUATION OF SPECKLE REDUCTION FILTERS FOR OPTICAL COHERENCE TOMOGRAPHY IMAGES - VENKATRAMAN.K; M.SUMATHI (International Journal of Pharma and Bio Sciences, 2015)
Medical Images play a vital role in the diagnosis of various diseases. Hence high resolution and reduced noise becomes vital while representing these images. The Medical imaging modalities using Ultrasound produces images which are affected by speckle noises which are multiplicative in nature, caused due to interference of the backscattered image. One such modality used in ophthalmology is the Optical Coherence Tomography. Various filtering techniques have been proposed to reduce these speckle noises by pertaining the required image information. This paper aims at evaluating various such proposed filters. OCT image acquired using Karl Zeiss was used for this purpose of evaluation. Various filters were tested for speckle affected OCT image and the performances of these filters were evaluated in terms of Mean Square Error, Signal to Noise Ratio, Peak Signal to Noise Ratio, and visual inspection. The system was designed using MATLAB, Intel core 2 duo processor and was tested with images obtained from a medical research center. Results show that homomorphic wiener filters show a better performance followed by Gaussian filters. The results of the tested system for OCT Images can also be generalized for any other ultrasound based modality images.